Volume 4: Nuclear Safety, Security, and Cyber Security; Computer Code Verification and Validation 2018
DOI: 10.1115/icone26-81759
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hydrogen Treatment System in Severe Accident: Part 4 — Study of Fission Products and Steam Effect on Hydrogen Treatment Characteristics

Abstract: A large amount of hydrogen is generated by the metal water-reaction in the Primary containment vessel (PCV) of light water reactors in the severe accident (SA). In the present accident management for boiling water reactor (BWR), vent of mixing gas with filtered vent is regarded as the most likely method that prevents the PCV overpressure. However, it is difficult to vent in early stage of SA because of high radioactive dose. Then we have been developing the hydrogen treatment system to prevent excessive pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that at relatively low temperatures (< 250 °C) the oxidation of hydrogen by CuO has an induction period of tens of minutes, but as the temperature approaches 250 °C the induction period becomes progressively shorter (Kim, et al, 2003). It has also been reported that the reaction rate decreases in atmospheres containing water vapor (Yamada, et al, 2015). However, the mechanisms underlying the process are not fully understood and current models fail to accurately simulate the empirically observed induction period.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that at relatively low temperatures (< 250 °C) the oxidation of hydrogen by CuO has an induction period of tens of minutes, but as the temperature approaches 250 °C the induction period becomes progressively shorter (Kim, et al, 2003). It has also been reported that the reaction rate decreases in atmospheres containing water vapor (Yamada, et al, 2015). However, the mechanisms underlying the process are not fully understood and current models fail to accurately simulate the empirically observed induction period.…”
Section: Introductionmentioning
confidence: 99%